Liver-Directed Therapy for Neuroendocrine Tumor Liver Metastases in the Era of Peptide Receptor Radionuclide Therapy - Lehrman, Evan D.; Fidelman, Nicholas (Seminars in Interventional Radiology, 2020)
Neuroendocrine tumor liver metastases are treated by a multidisciplinary cohort of physicians that work together to achieve optimal clinical results for their patients. This review addresses critical concepts in diagnosis and workup of such patients followed by medical, surgical, and liver-directed arterial and ablative therapies. Specific perioperative care for these patients is crucial in avoiding dreaded complications related to Carcinoid Crisis. The recent introduction of Peptide Receptor Radionuclide Therapy as a therapeutic option has impacted some of the algorithms for timing and selection of arterial embolotherapies.
Keywords: neuroendocrine tumor; carcinoid crisis; chemoembolization; radioembolization; bland embolization; ablation; peptide receptor radionuclide therapy